Leaving the South : Border Crossing Narratives and the Remaking of Southern Identity - Weaks-Baxter, Mary (Book collections on Project MUSE., 2019)
"Millions of southerners left the South in the twentieth century in a mass migration that has, in many ways, rewoven the fabric of American society on cultural, political, and economic levels. Because the movements of southerners--and people in general--are controlled not only by physical boundaries marked on a map but also by narratives that define movement, narrative is central in building and sustaining borders and in breaking them down. In Leaving the South: Border Crossing Narratives and the Remaking of Southern Identity, author Mary Weaks-Baxter analyzes narratives by and about those who left the South and how those narratives have remade what it means to be southern. Drawing from a broad range of narratives, including literature, newspaper articles, art, and music, Weaks-Baxter outlines how these displacement narratives challenged concepts of southern nationhood and redefined southern identity. Close attention is paid to how depictions of the South, particularly in the media and popular culture, prompted southerners to leave the region and changed perceptions of southerners to outsiders as well as how southerners saw themselves. Through an examination of narrative, Weaks-Baxter reveals the profound effect gender, race, and class have on the nature of the migrant's journey, the adjustment of the migrant, and the ultimate decision of the migrant either to stay put or return home, and connects the history of border crossings to the issues being considered in today's national landscape."--Provided by publisher.